Simplified Estimation Method for Maximum Deflection in Bending-Failure-Type Reinforced Concrete Beams Subjected to Collision Action and Its Application Range - Yusuke Kurihashi; Hiroshi Masuya (Applied Sciences, 2020)
As natural disasters have become increasingly severe, many structures designed to prevent rockfalls and landslides have been constructed in various areas. The impact resistance capacity of a reinforced concrete (RC) rock shed can be evaluated using its roof deflection. This study establishes a method for estimating the maximum deflection of a bending-failure-type RC beam, subjected to collisions that is based on the energy conservation concept—in which, the transmitted energy from a collision is equivalent to the energy absorbed by the beam. However, the following assumptions have never been confirmed: (1) The energy transmitted to the RC beam, due to the dropped weight, can be estimated by assuming a perfect plastic collision; and (2) the energy absorbed by the RC beam can be estimated by assuming plane conservation. In this study, these assumptions were verified using 134 previous test results of RC beams subject to weight collisions. In addition, we proposed a simple method for calculating the maximum deflection and its application scope. With this method, a performance-based impact-resistant design procedure for various RC structures can be established in the future. Moreover, this method will significantly improve the maintenance and management of existing RC structures subject to collisions.